Squirrels don't read, Shakespeare - Sculthorp, Jeffrey; Walter, Lorin (St. Paul, MN : Trend enterprises, 2000)
Shakespeare the Squirrel wants to read so much that he goes to his friend Albert the Owl in hopes he will teach him.
Keywords: Squirrels -- Fiction; Reading -- Fiction; Books and reading -- Fiction